Investigation by focused laser beam scanning of the photoelectric activity of bacteriorhodopsin-containing lipid bilayers. - Dancsházy, Z (1978)
The photoelectric activity of different parts of lipid bilayer containing bacteriorhodopsin was investigated by moving a small actinic light spot across the Plateau-Gibbs border and the bimolecular part of this reconstituted model membrane. The results give direct evidence that bacteriorhodopsin incorporated into the bimolecular region of the lipid membrane is responsible for the photoelectric activity of this system. A technique for scanning the photoelectric activity of a modified bimolecular lipid membrane is described in detail.